A collection explosion: finding our collection roots and examining how we got from there to here. Issue 4 (5th October 2015) - Laskowski, Mary S.; Maddox Abbott, Jennifer A.; Norman, Michael A.
Abstract : Purpose: – The purpose of this paper is to present research findings from a project to identify, locate and examine the first collection of a large academic research institution. The article also examines changes in collections over time and some of the factors influencing changing collection development policies and practice. Design/methodology/approach: – Methodology included historical archival research, collection discovery and item by item comparison. Findings: – As electronic access, shared repositories and access to shared content reshape the collection development landscape, the emphasis is shifting toward global access and unique local content. And yet, we see that this new model is built on a solid foundation of collection development almost 150 years in the making. Originality/value: – Understanding how the University Library got to where it is will help inform future decisions and directions regarding collection development, and allow others to compare our findings against their own institutional growth and forward trajectory.